Ruqyah Syar’iyah: Upaya Mencari Kesembuhan - Mukhtamar Hayat (Emik, 2020)
The treatment of ruqyah syar'iyah (hereinafter referred to as ruqyah) is one of the treatments practiced in time of Rasulullas SAW. In the last few years, such treatment has been popularly practiced in Indonesia, including in Makassar, one of the cities in Indonesia where the practice of ruqyah is mushrooming. While many literatures deal with the practice of ruqyah from spiritual point of view, the new contribution of this article lies in the practice of various types of ruqyah. This study was conducted in the city of Makassar, the capital city of South Sulawesi where more than 80% of its population are Muslims. Using qualitative approach, this study involved 14 informants, consisting of eight patients, two peruqyah, staff of ruqyah clinic and patients’ families respectively. Data was collected using the combination of interview and observation. This study shows that whether or not one is intended to cure his/herself depends very much on their belief in the treatment. Some started with modern medical treatment, others had full faith from the start. Some did it on the basis of their own desire, others influenced by close relatives. Ruqyah is part of Tibbun Nabawi and in its development ruqyah itself is divided into three types, namely, mass ruqyah, clinic ruqyah, and independent ruqyah. Despite the fact that the stages of each type are relatively the same: pra-ruqyah, main ruqyah, and post-ruqyah, each has its own uniqueness. Ruqyah not only helps to heal someone, especially those who suffer from disorders of spirits, but also strives to be a medium of preaching for patients. Curative healing is the main axis in the treatment of ruqyah, but preventive measures are also introduced as a bulwark against disturbance by spirits. Even though ruqyah is an islamic treatment, non-Muslim is not prohibit to take such treatment as long as they believe and follow the rule. This indicates that the belief to such treatment breaks down religious barriers. However, healing through ruqyah treatment is not entirely dependended on peruqyah, but it is mainly depended on the patient him/herself, by improving his/her quality of life after the ruqyah treatment.